Reducción de scrap en una industria plástica - Espol (2017)
Pack Solutions S.A. (fictitious name in order to preserve the confidentiality of the data) is a company that manufactures flexible polyethylene plastic packaging, and from the year 2014 to the present there have been high rates of scrap, especially in the area of extrusion. Therefore, the present work is focused on the reduction of the excess of waste that is generated in this area of the company. The objective of this project is to reduce the percentage of average waste in extrusion by 20%, because the company has a standard that limits this percentage and is not currently being met. For the development of the present project the DMAIC methodology was used, where in the first phase that is Define, customer needs were determined that later became variables that contributed significantly to quantify the problem. For the Measure phase, data were taken from the variables of interest, where we proceeded to analyze this information collected in work teams formed by operators and personnel involved in the process. In the Improvement phase, several proposals for improvement were proposed for root causes found that have the greatest impact on the problem. Finally, in the Control phase, actions were defined so that all proposed improvements would last through time. With the implementation of the standardization of the work change process and the design of a sequencing model using the S-DBR methodology, the scenarios of before and after the implementation were analyzed, obtaining as a result that the percentage of waste on average reduced by 45.40%.